2015
DOI: 10.3991/ijoe.v11i4.4742
|View full text |Cite
|
Sign up to set email alerts
|

On line and other Game-Based Learning for Mathematics

Abstract: Abstract!The last decade, researchers and educators have shown particular interest for the use of educational video games in mathematics education, in an effort to provide educational character to entertainment. In this paper we represent some of the most representative studies which evaluate the effects of video games on mathematics achievement as well as the improvement of memory, attention and cognitive skills. As indicated by the studies, video games may constitute useful tools in mathematics education as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…Also, the results showed that describing the game versus math drills experience, a higher proportion of children selected the attribute 'exciting' for their game playing experience and, likewise a higher proportion of the group that solved the paper math exercises selected the attribute 'boring' [12]. Drigas and Pappas (2015), in their review paper, examined the most representative studies over the last decade which evaluate the effects of video games on mathematics achievement and showed how video games support children's mathematic comprehension on fundamental concepts. Also, they investigated the different types of Online video games such as Educational Math Games, Adventure Games, Simulation Games and Mobile Video Games as well as Computer Video Games like Simulation Games, Srategy Games and Role-Playing Games presenting their positive effect on student's mathematical skills [16].…”
Section: Serious Games' Impact On Geometric and Mathematical Thinkingmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, the results showed that describing the game versus math drills experience, a higher proportion of children selected the attribute 'exciting' for their game playing experience and, likewise a higher proportion of the group that solved the paper math exercises selected the attribute 'boring' [12]. Drigas and Pappas (2015), in their review paper, examined the most representative studies over the last decade which evaluate the effects of video games on mathematics achievement and showed how video games support children's mathematic comprehension on fundamental concepts. Also, they investigated the different types of Online video games such as Educational Math Games, Adventure Games, Simulation Games and Mobile Video Games as well as Computer Video Games like Simulation Games, Srategy Games and Role-Playing Games presenting their positive effect on student's mathematical skills [16].…”
Section: Serious Games' Impact On Geometric and Mathematical Thinkingmentioning
confidence: 95%
“…Drigas and Pappas (2015), in their review paper, examined the most representative studies over the last decade which evaluate the effects of video games on mathematics achievement and showed how video games support children's mathematic comprehension on fundamental concepts. Also, they investigated the different types of Online video games such as Educational Math Games, Adventure Games, Simulation Games and Mobile Video Games as well as Computer Video Games like Simulation Games, Srategy Games and Role-Playing Games presenting their positive effect on student's mathematical skills [16].…”
Section: Serious Games' Impact On Geometric and Mathematical Thinkingmentioning
confidence: 99%
“…Considering the cognitive side, a review by Drigas and Pappas (2015) reports representative studies evaluating the effects of video games on mathematics achievement, memory, attention and cognitive skills. These studies indicate that video games can be useful in mathematics education, supporting the comprehension of fundamental concepts and motivating them to see positively mathematics.…”
Section: Game-based Learning and Assessment For Numerical Cognitionmentioning
confidence: 99%
“…Nowadays, Serious Educational Games are used for learning purposes in various schools' disciplines: languages, mathematics, natural sciences, medical sciences, etc. The authors of the [4] study over 30 papers on mathematics games; they view games as a tool to help students understand the fundamental concepts of mathematics, developing critical thinking and motivation method for their development in this discipline.…”
Section: Creating Serious Educational Games and Using Them For The Purposes Of Medical Educationmentioning
confidence: 99%